2017
DOI: 10.1186/s13017-017-0122-9
|View full text |Cite
|
Sign up to set email alerts
|

Acute appendicitis, inflammatory appendiceal mass and the risk of a hidden malignant tumor: a systematic review of the literature

Abstract: IntroductionAcute appendicitis is significantly common. Despite the increased use of computed tomography, the number of perforated cases has been stable in the past three decades. Between 2% and 6% of patients with acute appendicitis present appendiceal mass, often described as inflammatory phlegmon or abscess. Malignant tumors are confirmed by pathological analysis in 0.9–1.4% of all appendectomies performed to treat acute appendicitis. However, recent series demonstrate an elevated incidence of malignancies,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
98
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(110 citation statements)
references
References 58 publications
6
98
0
6
Order By: Relevance
“…Appendiceal tumors are rare, usually incidental findings most often detected at histological evaluation of the removed appendix. Appendiceal neoplasm rate varies from 0.7 to 2.5% of appendectomy specimens in several large appendectomy series [7,[11][12][13]. With the development of precise diagnostic capabilities like CT, appendiceal tumors may increasingly be suspected on CT [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Appendiceal tumors are rare, usually incidental findings most often detected at histological evaluation of the removed appendix. Appendiceal neoplasm rate varies from 0.7 to 2.5% of appendectomy specimens in several large appendectomy series [7,[11][12][13]. With the development of precise diagnostic capabilities like CT, appendiceal tumors may increasingly be suspected on CT [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The SEER‐Medicare database is limited to only retrospective analysis and is subject to incomplete information secondary to clerical errors including erroneous coding or improper database entry. In addition, other studies have suggested that a prolonged duration of appendicitis, specific computed tomography (CT) findings or an atypical presentation may be suggestive of appendiceal cancer over inflammatory appendicitis, however, presentation data is not captured from the study database …”
Section: Discussionmentioning
confidence: 99%
“…A patient with mixt carcinoid adenocarcinoma was found to be 30% of The distribution performed surgical treatments of benign and malign appendiceal tumor types is given in 15 In a study conducted in our country, it was reported that the incidence of premalignant lesions and malign neoplasms in samples taken after appendectomy were 0.5 and 0.6, respectively. 16 In our study, the incidence of the malign appendiceal tumor was found to be quite low compared to other studies.…”
Section: Introductionmentioning
confidence: 99%